Image encryption algorithm based on improved Clifford chaotic system - Zhang Wenyu; Xing Rongying; Li Guodong (Dianzi Jishu Yingyong, 2022)
Information security is an increasingly concerned issue. As the carrier of information transmission, digital image contains a large amount of information. In order to improve the security of digital image transmission, this paper improves the Clifford system, analyzes the chaotic characteristics of Clifford system through chaotic attractor graph and Lyapunov exponent, and designs a new image encryption algorithm based on the improved Clifford system. Firstly, the plaintext is transformed into a binary matrix. The rows and columns of the binary matrix are circularly shifted. Then, the plaintext is divided into nine matrix blocks with different sizes, and each matrix block is scrambled. In block scrambling, chaotic sequences are used to scramble between blocks, while cyclic displacement scrambling is used to scramble within blocks which ensures that the position of each pixel has changed. Finally, the image is diffused to get the ciphertext. Simulation experiments and security analysis show that the algorithm is safe and reliable for image encryption.